The Effectiveness of Son-Rise Program on Improving Social Interactions and Communication Status among the Children with Autism - Sahar Jasemi; Mina Ahmadi-Kahjoogh; Mehdi Rahgozar; Ebrahim Pishyareh (Vesnu Publications, 2018)
Introduction: Autism affects the person's ability to communicate with others, and appropriate response to the outside environment. One of the therapeutic approaches in children with autism is the Son-Rise Program. The aim of this study was to evaluate the effectiveness of the Son-Rise Program on improving social interactions and communication status among the children with autism. Materials and Methods: This was a quasi-experimental study with pretest and posttest design, and a control group. 30 children with autism were selected using convenience sampling method, and were assigned randomly to equal groups of experimental (with intensive Son-Rise Program) and control (with common rehabilitation interventions). The Gilliam Autism Rating Scale (GARS2) and the Vineland Social Maturity Scale (VSMS) were used as pretest for assessment, and Gilliam Autism Rating Scale was use for re-evaluation. Paired and independent t tests were used for statistical analysis. Results: The Son-Rise Program had a significant effect on the social interaction of children with autism compared with common rehabilitation interventions (P = 0.001). In addition, the effect of this approach on communication status in children with autism was not significant compared to the control group (P = 0.110). Conclusion: It can be concluded that Son-Rise Program could improve social interaction in children with autism. However, the influence of this program on communication status among this group of children needs to be assessed more in future interventional clinical trial studies with larger sample sizes.